A rare case of adult rhabdomyosarcoma with adnexal metastasis responding tonon-conventional chemotherapy (Indian Journal of Case Reports, 2024)
Rhabdomyosarcoma (RMS) is a pediatric soft tissue sarcoma having a rare incidence among adults. It is a highly chemo-radiosensitive tumor among the pediatric population but has poor biology in adults with dismal outcomes. Due to the rarity of adult RMS, there are no well-defined treatment guidelines for adult RMS and are mostly managed with pediatric-defined protocols but lack similar response. Here, we present the case of an adult female with extremely atypical metastatic site RMS which showed an extraordinary response to non-pediatric protocol, rather than adult sarcoma-based protocol. This might give an idea to have more research and trials in the future to implement adult sarcoma-based therapy among adult RMS cases.